2015
DOI: 10.1093/aobpla/plw064
|View full text |Cite
|
Sign up to set email alerts
|

Correlations of polyploidy and apomixis with elevation and associated environmental gradients in an alpine plant

Abstract: We are presenting a study on geographical parthenogenesis, an enigmatic and much disputed phenomenon. Based on a large sampling of natural populations of Ranunculus kuepferi, it is the first quantitative, population-based assessment of mode of reproduction throughout the Alps to test for correlations to elevation and to geographical distance patterns. Surprisingly, we found a high variance in the modes of reproduction among cytotypes and can give the first evidence of apomixis in diploid natural populations. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
166
2
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(178 citation statements)
references
References 90 publications
(146 reference statements)
9
166
2
1
Order By: Relevance
“…Drought was identified as a factor driving the pattern in Draba (Price, ), Antennaria (Bierzychudek, ), Bidens (Crowe & Parker, ), Paspalum intermedium (Karunarathne et al, ), and the Ranunculus auricomus complex (Paule et al, ). The opposite pattern, however, was found in this study: Sexual P. puberula prevailed at drier sites, a tendency also observed in Ranunculus kuepferi (Schinkel et al, ). This might be explained by the negative effects of rainy weather on pollinators’ behavior (Puškadija et al, ), which avoid flying under the rain or foraging on wet blossoms.…”
Section: Discussioncontrasting
confidence: 71%
See 2 more Smart Citations
“…Drought was identified as a factor driving the pattern in Draba (Price, ), Antennaria (Bierzychudek, ), Bidens (Crowe & Parker, ), Paspalum intermedium (Karunarathne et al, ), and the Ranunculus auricomus complex (Paule et al, ). The opposite pattern, however, was found in this study: Sexual P. puberula prevailed at drier sites, a tendency also observed in Ranunculus kuepferi (Schinkel et al, ). This might be explained by the negative effects of rainy weather on pollinators’ behavior (Puškadija et al, ), which avoid flying under the rain or foraging on wet blossoms.…”
Section: Discussioncontrasting
confidence: 71%
“…Studies dealing with these issues often remained inconclusive, due to limitations inherent to the studied taxa, such as lack of cytotypic variation within reproductive mode or different evolutionary history of sexuals and apomicts (see Supporting Information Table A5 in Appendix for a review of ecological studies in amphi‐apomictic systems). For instance, Schinkel et al, () found apomictic individuals in three pure diploid populations of Ranunculus kuepferi , which shared the ecological site conditions of co‐occurring sexuals. However, their number was not high enough to prove that polyploidy was a requirement for range expansion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon has long been viewed as an outcome of selective pressure during postglacial recolonization, where polyploid identities (combined in part with apomixis) are seen to facilitate adaptive leading‐edge population dispersal into novel habitats (Bliss ), and there is now some empirical support for this proposition (Schinkel et al . ).…”
Section: Introductionmentioning
confidence: 97%
“…It has long been recognized that asexual reproduction (vegetative propagation and agamospermy) and WGD are correlated, with polyploids displaying elevated rates of asexual propagation compared to diploid relatives (Manning and Dickson, 1986;Schinkel et al, 2016;Herben et al, 2017). Such a reproductive strategy may even confer short-term benefits.…”
Section: The Short-term Challenges Meiosismentioning
confidence: 99%